Meningkatkan Motivasi Belajar Melalui Penerapan Model Belajar Jigsaw - Zarkasi, Takiudin (Al-Riwayah : Jurnal Kependidikan, 2018)
This paper discusses the increasing students’ learning motivation using a new learning model known as jigsaw learning on the subject of the Quran Hadith. The results of this study shows that the jigsaw method can foster students' learning motivation by itself, because in this study it provides an opportunity for all students to be actively involved in the thinking process and learning activities. By providing many opportunities for students to actively learn the group in memorizing short letters to make the students' ability to read and memorize to be good because there is a process of brainstorming and complementary reading and memorizing students.